A comprehensive risk management framework for NIMBY projects: Integrating social network analysis and risk transmission chains - Jian Xu; Ran Ling; Milun Yang; Ronge Miao; Huan Zhou; Huixuan Xiang; Yu Jing; Ruiqu Ma; Genyu Xu (Ecological Indicators)
Urban development projects often face local opposition, known as the NIMBY (Not in my back yard) effect, affecting infrastructure implementation and urban growth. This study aims to develop a systematic risk management approach for NIMBY projects. Employing grounded theory, 29 NIMBY cases in China were analyzed, identifying 17 risk factors across six categories. Social network analysis revealed risk interactions, highlighting four factors: government decision-making risk, government credibility risk, project completion risk, and online public opinion risk. Two risk transmission chains were delineated, each consisting of 4–5 interconnected risk factors, providing insights into risk propagation mechanisms. Simulation results indicated that targeted risk mitigation strategies based on these chains affected network efficiency differently compared to random approaches. The network efficiency reduced from 16.5% to 11.2% for the first chain-based strategy and to 13.4% for the second, while random interventions showed limited impact on network efficiency. Based on these findings, a NIMBY risk management system focusing on risk nodes and incorporating risk compensation mechanisms is proposed. This system addresses proactive governance, stakeholder engagement, and risk mitigation. The research contributes to the understanding and management of NIMBY risks, providing tools for policymakers and project managers. The findings suggest that this approach may affect NIMBY conflicts and community acceptance of urban development projects, potentially influencing urban development processes.